Microeconomic Essentials : Understanding Economics in the News - Prag, Jay (Cambridge, Massachusetts : MIT Press, 2020)
"An introduction to microeconomics for introductory/non-major micro and MBA courses"--
Includes index.
Keywords: Microeconomics